2023
DOI: 10.1186/s13613-023-01102-3
|View full text |Cite
|
Sign up to set email alerts
|

Critically ill patient mortality by age: long-term follow-up (CIMbA-LT)

Abstract: Background The past years have witnessed dramatic changes in the population admitted to the intensive care unit (ICU). Older and sicker patients are now commonly treated in this setting due to the newly available sophisticated life support. However, the short- and long-term benefit of this strategy is scarcely studied. Methods The Critically Ill patients’ mortality by age: Long-Term follow-up (CIMbA-LT) was a multicentric, nationwide, retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Because of the newly accessible sophisticated life support, an increasing number of older and more severely ill patients are receiving treatment in this environment. However, such patients are associated with elevated all-cause mortality rates [ 26 ]. In our study, the in-hospital mortality rate for critically ill older patients was found to be 18.8%, and this mortality was similar to other investigations reported.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the newly accessible sophisticated life support, an increasing number of older and more severely ill patients are receiving treatment in this environment. However, such patients are associated with elevated all-cause mortality rates [ 26 ]. In our study, the in-hospital mortality rate for critically ill older patients was found to be 18.8%, and this mortality was similar to other investigations reported.…”
Section: Discussionmentioning
confidence: 99%
“…The rising burden of critical illness around the world and the demand for more ICU beds underscore the urgency for research aiming to improve outcomes for critically ill patients. 180 With mortality rates around 16% in the critically ill, 181 addressing disruptions in circadian rhythms-crucial to physiological homeostasis-is imperative. The ICU environment and postoperative care often disturb these rhythms due to the absence of natural cues such as light, regular meals, and physical activity.…”
Section: Translation-light Therapy For Cardiovascular Disease In Humansmentioning
confidence: 99%
“…This increase in hospitalization days implies an increase in hospitalization costs [ 22 , 30 , 47 ]. Furthermore, the one study from Portugal included in our review reported a median ICU LOS value of nine days (7.00 - 12.00), while another study examining the period from January 2015 to June 2019 in Portugal reported a median ICU LOS value of four days (2.00 - 9.00) [ 37 , 48 ]. The study from India included in our analysis reported a mean ICU LOS value of nine days (IQR: 5-13).…”
Section: Reviewmentioning
confidence: 99%